Concentration- and nutrient-dependent cellular responses of microalgae Chlorella pyrenoidosa to perfluorooctanoic acid. (15th October 2020) - Hu, Yi; Meng, Fan-Li; Hu, Yan-Yun; Habibul, Nuzahat; Sheng, Guo-Ping
Highlights: Algal response to PFOA in various concentration and nutrient levels was studied. PFOA at concentrations less than 1.0 mg/L had no obvious toxicity on C. pyrenoidosa . Nutrient conditions influenced the response of C. pyrenoidosa to 1.0 mg/L PFOA. The adsorbed and ingested PFOA by C. pyrenoidosa were both less than 10%. Nutrient conditions enhanced PFOA adsorption but reduced uptake by C. pyrenoidosa . Abstract: Perfluorooctanoic acid (PFOA), an emerging and persistent pollutant, could cause toxicity effects on aquatic organisms. However, this was generally assessed under high exposure concentrations of PFOA and nutrient-enriched conditions, which was not accordant with the actual environments. Therefore, to comprehensively understand the toxicity effects of PFOA on aquatic organisms, the cellular responses of microalgae, Chlorella pyrenoidosa, to PFOA under different concentrations (≤ 1.0 mg/L) and nutrient conditions were investigated in this study. Results show that PFOA at concentrations less than 1.0 mg/L had no significant effects on algal growth and chlorophyll contents, and no oxidative damages were generated to destroy membrane integrity and morphology. However, N, P-limited and -starved conditions significantly decreased algal growth and chlorophyll contents, and induced oxidative stresses to ruin the structure and function of cell membrane. Moreover, the deficiency of P had more severe negative effect on algae than that of N, and they both influenced the toxicity responses of microalgae to 1.0 mg/L PFOA. The adsorption and uptake percentages of PFOA by algal cells were both less than 10%, and increased adsorption but decreased uptake of PFOA amounts occurred under N, P-limited and -starved conditions. These findings will be useful to understand the toxicity effects of PFOA on microalgae in aquatic environments. Graphical abstract: Image, graphical abstract